PERLINDUNGAN HUKUM TERHADAP ANAK DI BAWAH UMUR YANG MENGAJUKAN DISPENSASI NIKAH - Parera, Rikser (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: As stated in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage which states that there is an exception to apply for marriage dispensation as a condition of the minimum age limit. In fact, many minors apply for marriage compensation for being pregnant out of wedlock and forced to marry to restore the family's good name. This highlights the benefits of Law Number 35 of 2014 concerning child protection. Using normative juridical methods through literature studies discussing the implementation of the Marriage Law and the Child Protection Law, to strengthen the protection of the rights of children who apply for marriage dispensation, one of which is by providing legal and psychological assistance for minors who apply for marriage dispensation.Keywords: Protection, Law, Child, Married.